Presence of the pregnant partner regulates microRNA-30a and BDNF levels and protects male mice from social defeat-induced abnormal behaviors. (15th November 2019) - Miao, Zhuang; Zhang, Jianghong; Li, Yuanyuan; Li, Xianfeng; Song, Wei; Sun, Zhong Sheng; Wang, Yan
Abstract: Consolation behavior within close social bonds can alleviate the negative effects of stressful events on individuals. Due to the lack of animal models, however, its underlying mechanisms remain poorly explored. Moreover, most social support effects are exerted through grooming or consolation behavior from close social bonds, whether pure companionship without physical interaction exert effects still remains unknown. Here, we report that among the most widely used laboratory mouse, social avoidance and anxiety-related behaviors induced by chronic social defeat stress (CSDS) were alleviated by the presence of their pregnant partner without body contact during the stress process, whereas non-pregnant females did not afford similar protective effect to the male partner. The levels of BDNF, together with its primary transcripts, were down-regulated in the hippocampus of male mice with CSDS and these decreases were ameliorated by the presence of their pregnant partners. Furthermore, miR-30a negatively regulated BDNF expression and the regulation of miR-30a was implicated in the supporting effect on the male mice experiencing CSDS. The identification of psychological protective effects in a primary model organism and its underlying mechanism would promote our understanding how people cope with stress-induced psychiatric disorders independent of anti-depressant drugs and facilitate investigation of the molecular mechanisms of enduring social bonds in humans. This article is part of the Special Issue entitled 'The neuropharmacology of social behavior: from bench to bedside'. Highlights: The presence of pregnant partner protects male mice from adverse behaviors. Hippocampal BDNF levels negatively correlates with avoidance and anxiety behaviors. miR-30a negatively regulated the levels of BDNF. Hippocampal miR-30a injection in mice mimics social defeat-induced behaviors.